Arthur Danto and Art world - I. N. Nekhaeva (Омский научный вестник: Серия "Общество. История. Современность")
The American philosopher Arthur Danto left a bright mark in the history of contemporary art as his analyst, critic and even artist. In the mid-1960s, Arthur Danto first introduced the analytical method to the field of philosophy of art in order to evaluate the heuristic capacities and ways of applying analytical tools to the art. Deep vision into the very essence of the transformations that shook the art of the 1960s, and keen interest in the work of artists of conceptual pop art, it’s all pushed Arthur Danto to study the problems of language boundaries in the art. The concept of Art as the independent World with its laws and transformations allowed Arthur Danto not only to eliminate the problem of definition of art, but also to present a holistic picture of the development of art of the late 20th century